Political economy of social protection in Sub-Saharan Africa and in Madagascar : contribution of social network analysis - (:unkn) unknown (My University, 2022)
This thesis proposes to study the development of social protection systems in sub-Saharan Africa. We consider social protection systems as multi-levels (i.e. transnational, national, local) and multi-actors sets. We analyse these different levels of social protection by mobilizing a socio-economic approach which uses social network analysis. This approach allows us to take into account the reticular and negotiated aspect of the different levels of social protection. We therefore propose to study the transnational level by identifying the three main social protection regimes and by analysing the role of national and international power relations. At the national level, we study the implementation of social protection in Madagascar. To examine the influence of transnational coalitions in the implementation of social protection policy in sub-Saharan Africa, we use policy network and advocacy coalition framework methods. Finally, at the local level, we study the role of reciprocity norms in household social protection practices. To that end, we analyse the egocentric shock management networks developed by households. We characterise three forms of reciprocity (symmetrical, asymmetrical and absence of reciprocity) according to household livehoods and support networks.
Keywords: African Research